The carbon balance of forest biomes - Griffiths, H. (Howard), 1953-; Jarvis, P. G. (Paul Gordon) (Experimental biology reviews., 2005)
The Carbon Balance of Forest Biomes provides an informed synthesis on the current status of forests and their future potential for carbon sequestration. This volume is timely, since convincing models which scale from local to regional carbon fluxes are needed to support these international agreements, whilst criticisms have been levelled at existing empirical approaches. One key question is to determine how well eddy-flux measurements at the stand-level represent regional-scale processes. This may be related to specific management practices (age, plantation, fertilisation) or.